CONSUMPTION AND UTILIZATION OF SENESCENT FLOWERS BY MYLABRIS PUSTULATA (COLEOPTERA) - KRISHNAN, N.; JEYAKUMAR, G.; DINAKARAN, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
Food utilization indices of the female Mylabris pustulata Thunb (511-512 mg/live wt) were estimated on normal (collected shortly after anthesis at 6 a.m.) as well senescent (collected after 12hrs of anthesis at 6 p.m.) flowers of Ipomoea cornea and I. tuberosa for 25 days at 29 ± 10C and 70% RH. The assimilation (AD), gros (ECD and net (ECD) conversion efficiencies of the beetle decline while consumption (C) and metabolism (M) were increased on senescent flowers of both hosts. Feeding on normal as well as senescent flowers of I. tuberosa resulted in high AD, ECI and ECD decreased to a minimum level on senescent flowers. These results were discussed on the basis of reduction in proteins and waterinaged flowers.